COMPARATIVE ANALYSIS OF CONTRACTS FOR THE TRANSFER OF RESIDENTIAL PREMISES FOR USE - NIKULINA S.A. (Legal Bulletin)
The article examines the contracts stipulated by the current legislation that regulate relations on transfer of residential premises for use. The author determines the list of such contracts, analyzes their content highlighting the distinctive features of each contract in comparison with each other. The object of the study is public relations arising between the parties in connection with the transfer of residential premises for use. The subject of the study is the current civil and housing legislation of the Russian Federation, as well as legal acts of all levels in the field of regulation of relations on transfer of residential premises for use. The purpose of the work is to carry out a comparative analysis of all contracts on transfer of residential premises for use and to identify their distinctive features for each comparative criterion. The methodological basis is made up of general scientific and special methods of cognition, such as: dialectical, formal-legal, structural-functional, as well as analysis, synthesis, comparison, deduction. The author identifies a large number of criteria for comparison, by means of which the content of each contract is disclosed in sufficient detail. At the same time, the author conducts a comparative analysis, comparing contracts with each other, in order to demonstrate their distinctive features. The main conclusion of the work is the identification of similar and different features of contracts for the transfer of residential premises for use. The author’s contribution is the analysis of 7 contracts for the transfer of residential premises according to 19 criteria, which clearly demonstrates that they differ in their legal nature and regulation of relations in this area. This comparative analysis is necessary for a detailed understanding of the complex social relations arising in connection with the transfer of residential premises for use.